Evaluation of Storage, Packaging and Transportation in The Management of Hazardous and Toxic Waste (B3) at PT X Batam City in 2024 - Sari, Novela; Harlen, Ridzqi; Yustisia Sembiring, Firdaus; Oktarizal, Hengky (Jurnal KESANS : Kesehatan dan Sains, 2025)
This study aims to evaluate the non-conformity of hazardous waste packaging aspects and infrastructure facilities with the Minister of Environment and Forestry Regulation Number 6 of 2021 concerning Procedures and Requirements for Hazardous and Toxic Waste Management. This research uses a qualitative descriptive method with data collected through interviews, observation, and documentation. Data analysis was carried out using triangulation techniques and this research involved 8 informants who were responsible for the management of B3 waste. The results showed that the management of B3 waste at PT X has not fully met the applicable regulations. Several problems were found, such as rusty packaging conditions, leaking waste packaging, and unstable packaging lids, which led to the scattering of B3 waste. In addition, there are inappropriate infrastructure facilities, such as the presence of a rest area in the B3 waste storage building, which should not be permitted. The conclusion of this study is that Human Resources (HR) involved in hazardous waste management need to increase awareness regarding the handling of hazardous waste in accordance with PERMEN-LHK regulation No. 6 of 2021. Improving the quality of human resources is very important because it determines the success of performance in achieving the company's vision and mission.